Proceedings of the Third International Conference on Economic and Business Management (FEBM 2018) 2018
DOI: 10.2991/febm-18.2018.96
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Study on Smart City Strategies in Berlin and Shanghai

Abstract: 1-Within the framework of this paper the classical approach of strategic management theory shifts its thematic focus from business organizations towards an even more complex system, namely that of cities. As a significant example of urban development approaches, the smart city model has gained large attention by policy makers around the world. In the early 2010s, both, Shanghai and Berlin, implemented their own smart city strategies with the aim of establishing themselves as the leading smart city within their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Comparing Study on Smart City Strategies in Berlin and Shanghai (Reiber and Huang, 2018).    0 Cybersecurity Strategy for Smart City Implementation (Alam and Ibrahim, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing Study on Smart City Strategies in Berlin and Shanghai (Reiber and Huang, 2018).    0 Cybersecurity Strategy for Smart City Implementation (Alam and Ibrahim, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Existing studies have been carried out on smart city strategies via case studies [33][34][35][36][37]. However, this study's methodological approach was a lifecycle-based smart city sustainable strategy, focusing more on best practices, lessons learned, and lifecycle phases for implementing the proposed model.…”
Section: Research Approach and Rationalementioning
confidence: 99%
“…Appraising smart sustainable city strategies, projects, and initiatives via a lifecycle approach is essential due to the provision of a structured pathway to arrive at the comprehension and knowledge regarding the implementation of the phases/stages, in addition to opportunities for continuous review and monitoring. The identified extant studies [31, [34][35][36][37] via a comprehensive literature review revealed that this study's lifecyclebased framework for smart city implementation is a prominent feature of strategy construction. However, the findings regarding the top-down and collaborative approach being the most widely utilized methodology for establishing smart city strategies agrees with smart sustainable cities-related studies [35].…”
mentioning
confidence: 99%
“…Bike sharing. Bike rental services that substitute for private automobile ownership [11,[20][21][22]26,27,34,42]; A3. Low-power electric vehicle sharing.…”
Section: Evaluation Criteria Of the Smart Mobility Systemmentioning
confidence: 99%